The probiotic and immunomodulation effects of Limosilactobacillus reuteri RGW1 isolated from calf feces - Huang, Kailang; Shi, Weibing; Yang, Bin; Wang, Jiakun (Frontiers in Cellular and Infection Microbiology, 2023)
Limosilactobacillus reuteri is a gut symbiont with multiple remarkable beneficial effects on host health, and members of L. reuteri are valuable probiotic agents. However, L. reuteri showed obvious host specificity. In our study, a novel L. reuteri RGW1 was isolated from feces of healthy calves, and its potential as a probiotic candidate were assessed, by combining in vitro, in vivo experiments and genomic analysis. RGW1 was sensitive to all the antibiotics tested, and it did not contain any virulence factor-coding genes. This isolate showed good tolerance to acid (pH 3.0), 0.3% bile salt, and simulated gastric fluid. Moreover, this isolate showed a high hydrophobicity index (73.7  4.6%) and was able to adhere to Caco-2 cells, and antagonize Escherichia coli F5. Treatment of LPS-induced mice with RGW1 elevated TGF- and IL-10 levels, while RGW1 cell-free supernatant (RCS) decreased TNF-α levels in the sera. Both RGW1 and RCS increased the villus height and villus height/crypt depth ratio of colon. Genomic analysis revealed the mechanism of the probiotic properties described above, and identified the capacity of RGW1 to biosynthesize L-lysine, folate, cobalamin and reuterin de novo. Our study demonstrated the novel bovine origin L. reuteri RGW1 had multiple probiotic characteristics and immunomodulation effects, and provided a deeper understanding of the relationship between these probiotic properties and genetic features.